Deactivation and Regeneration of Ni/ZA Catalyst in Hydrocracking of Polypropylene - Imam Khabib; Sri Kadarwati; Sri Wahyuni (Indonesian Journal of Chemistry, 2014)
The phenomena of catalyst deactivation and the effects of regeneration method on the characteristics and activity of Ni/ZA catalyst after being used in a continuous cracking reaction of polypropylene have been studied. Ni/ZA catalyst was prepared using sonochemical method with total metal intake of 4%. Characteristics and activity of fresh, spent, and regenerated catalyst were evaluated to get a better understanding about the catalyst deactivation. Characteristics which have been observed include catalyst acidity, porosity, crystallinity, and surface morphology. Catalytic activity test of Ni/ZA catalyst on polypropylene cracking reaction at temperature of 500 °C with H2 flow rate of 20 mL/min and catalyst:feed ratio of 1:2 (w/w) showed the decrease of some catalyst characteristics such as specific surface area, total pore volume, and acidity due to coke fouling over a five-times continuous experiment. Regeneration of catalyst with oxidation-reduction method has been able to increase the activity and acidity of catalyst up to 7.47% and 38.54%, respectively, compared to those of spent catalyst, while the catalyst surface area and total pore volume decreased up to 32.83% and 26.92%, respectively.